ComBox - Hårdvaruspecifikation - Bryne, Stefan (My University, 2015)
This document specifies the hardware of ComBox, a communication device for reading and writing data to an electronic unit, such as vehicles, via its CAN or ISO-9141 interface. Here are block diagrams, component choices and descriptions of ports, power supply, memories and communication entities and connector pin specifications. Lastly a paragraph on how ComBox would have turned out if it was designed today. A brief comparison of some important leap of technology that would have made ComBox easier, more efficient and more user friendly as a product. Thereafter follows an appendix showing a memory map of all entities inside ComBox containing information on addresses, bit widths and what decoder signal used. The following appendix includes a list of components used in the ComBox design as well as a cost calculation.
Keywords: Data- och informationsvetenskap; Computer and Information Science